Bowel Injury following Illegal Abortion : An Unusual Case (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
A rare and life threatening complication of induced abortion is bowel injury. Bowel resection with exteriorization of bowel with possibility of permanent stomas is the treatment, especially when the patient presents late. A 26 year old woman presented with peritonitis and fecal discharge per vaginum 1 week after an illegal abortion. Laparotomy revealed uterine perforation and colonic injury with the fetal head retained intraperitoneally . DOI: http://dx.doi.org/10.3329/bjog.v26i1.13761 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(1) : 48-49